2018
DOI: 10.1007/s40368-018-0359-3
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion prevention through the usage of an orthodontic pacifier compared to a conventional pacifier: a systematic review

Abstract: The currently available evidence is insufficient to support the concept that the usage of orthodontic pacifiers is able to prevent malocclusion traits when compared to the usage of conventional pacifiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Another recent systematic review [12] including five trials about the comparison between orthodontic and conventional pacifiers [6, 7, 10, 13, 14] concludes that a proper definition for a functional or orthodontic pacifier is missing, and that functional orthodontic pacifiers seem to cause less anterior open bite than conventional ones, while the no statistical difference implies the absence of an association between the prevalence of posterior crossbite and the use of orthodontic pacifiers [6, 10]. Thus, the main conclusion stated the insufficiency of currently available evidence to support this hypothesis that the usage of orthodontic pacifiers is able to prevent malocclusion traits when compared to conventional ones, and that new data on orthodontic pacifiers effects are necessary in literature to substantiate the argument [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent systematic review [12] including five trials about the comparison between orthodontic and conventional pacifiers [6, 7, 10, 13, 14] concludes that a proper definition for a functional or orthodontic pacifier is missing, and that functional orthodontic pacifiers seem to cause less anterior open bite than conventional ones, while the no statistical difference implies the absence of an association between the prevalence of posterior crossbite and the use of orthodontic pacifiers [6, 10]. Thus, the main conclusion stated the insufficiency of currently available evidence to support this hypothesis that the usage of orthodontic pacifiers is able to prevent malocclusion traits when compared to conventional ones, and that new data on orthodontic pacifiers effects are necessary in literature to substantiate the argument [8].…”
Section: Introductionmentioning
confidence: 99%
“…Malocclusion and sucking habits in children Massignan et al Malocclusion and sucking habits in children Massignan et al review observed that irrespective of the pacifier shape, children that had the habit of sucking pacifier experienced higher prevalence of malocclusion traits when compared to those that did not had the habit. 21 Auto correction of AOB is reported to occur if the habit is abandoned up to 4-6 years of age, 22 although the American Academy of Pediatric Dentistry recommends children stopping sucking habits up to 36 months old or younger. 23 Nevertheless it is important to address that breastfeeding could reduce the risk of developing maloclusion, 11 although in the present study this association was not found.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the skeletal and dental deformities, the continuous use of pacifier can lead to several myofunctional impairments, such as labial incompetence, lip entrapment, and decreased muscular tonicity. 15 16 17…”
Section: Methodsmentioning
confidence: 99%
“…The ideal time for usage is when the infant is asleep. 16 The characteristic features that accompany the extended use of pacifiers are constriction of the superior dental arch, especially at the area of the canine teeth, along with the enlargement of the inferior dental arch. 17 Due to the constant sucking action, the tongue is in a lower position in the oral cavity 15 .…”
Section: Use Of Pacifiers and Bottle Feeding And Its Role In Malocclusionmentioning
confidence: 99%
See 1 more Smart Citation